MODEL OF STRATEGIC ANALYSIS OF FORMATION AND ADMINISTRATION OF INVESTMENT ACTIVITY OF STOCKHOLDER CONSTRUCTION COMPANY - Iu. Chupryna (Astana IT University, 2020)
The article analyzes the market position of construction companies and builds a justification for updated methodological and analytical tools for evaluating, selecting, and building a productive system of portfolio administration of housing projects, which are implemented in a single operating system of the development company. The problems of investment activity of stakeholder construction companies, which have been constantly carried out in many countries by prominent foreign and domestic scientists, have been studied. Several variants of circumstances that shape the external and internal environment of the developer are analyzed, which must be taken into account when determining the strengths and weaknesses of the enterprise, its capabilities and threats, which provides a general picture of the internal situation and is important for developing optimal strategy for the enterprise. The operating system is determined by the introduction of fundamentally new updated scientific and applied tools designed to provide the development company with a clear formalization and proper analytical support of the processes of formation, analysis, and productive subsequent administration: the leading innovation of the tools introduced commercial housing construction, which are implemented in a complex economic and managerial format – production-technological, resource-logistical and administrative management of the content of business processes of project cycles as part of the portfolio of housing construction projects of the developer.